Blue applicability grade index assessment and response surface modelling to synchronous determination of metformin hydrochloride, vildagliptin and dapagliflozin propanediol monohydrate by HPTLC method - Pintu Prajapati; Krutika Patil; Dhrumi Naik; Veera Shakar Pulusu; Anzarul Haque; Mohd Abul Kalam; Shailesh Shah (Future Journal of Pharmaceutical Sciences)
Abstract Diabetes mellitus is major chronic disease found in human due to stressful lifestyle and bad food habit. Recently, the Central Drugs Standard Control Organization of India has approved combination of metformin hydrochloride, vildagliptin and dapagliflozin propanediol monohydrate for the management of diabetes mellitus. Numerous chromatographic methods have been published in the literature for estimation of these anti-diabetic drugs on individual basis and their combinations. But these chromatographic analyses promoted usage of toxic organic solvents which are harmful to the environment and aquatic animal lives. In addition, no chromatographic method was found in the literature for simultaneous estimation of these anti-diabetic drugs using green solvents. In recent days, white analytical chemistry approach has been introduced in the literature for development and assessment of green, accurate, precise, cost-effective and user-friendly chromatographic methods. Hence, white analytical chemistry-driven risk-based HPTLC method was developed for synchronous estimation of these anti-diabetic drugs using green solvents and response surface modelling. The analytical quality risk assessment was applied for identification of critical method variables and response variables using risk priority number ranking and filtering method. The critical method variables were linked with critical response variables using response surface modelling by Box–Behnken design. The analytical design space was navigated control strategy was framed for robust densitometric estimation of anti-diabetic drugs. The chromatographic method was validated as per ICH Q2 (R2) guideline. The developed method was applied for synchronous assay of multiple combinations of metformin, vildagliptin and dapagliflozin using single chromatographic condition to save time, cost and resources for analysis. The assay results of these anti-diabetic drug combinations were found to be complied with the respective labelled claim of the drugs. The developed and published chromatographic methods were assessed for their redness, greenness, blueness and whiteness profiles using green analytical metrics and RGB model scoring system. The proposed method was found to be green, cost-effective, robust and user-friendly for synchronous estimation of metformin, vildagliptin and dapagliflozin.